Serotonin/Dopamine Interactions in a Hyperactive Mouse: Reduced Serotonin Receptor 1B Activity Reverses Effects of Dopamine Transporter Knockout - Hall, Frank Scott (PLoS One, 2014)
Knockout (KO) mice that lack the dopamine transporter (SL6A3; DAT) display increased locomotion that can be attenuated, under some circumstances, by administration of drugs that normally produce psychostimulant-like effects, such as amphetamine and methylphenidate. These results have led to suggestions that DAT KO mice may model features of attention deficit hyperactivity disorder (ADHD) and that these drugs may act upon serotonin (5-HT) systems to produce these unusual locomotor decreasing effects. Evidence from patterns of brain expression and initial pharmacologic studies led us to use genetic and pharmacologic approaches to examine the influence of altered 5-HT(1B) receptor activity on hyperactivity in DAT KO mice. Heterozygous 5-HT(1B) KO and pharmacologic 5-HT(1B) antagonism both attenuated locomotor hyperactivity in DAT KO mice. Furthermore, DAT KO mice with reduced, but not eliminated, 5-HT(1B) receptor expression regained cocaine-stimulated locomotion, which was absent in DAT KO mice with normal levels of 5-HT(1B) receptor expression. Further experiments demonstrated that the degree of habituation to the testing apparatus determined whether cocaine had no effect on locomotion in DAT KO or reduced locomotion, helping to resolve differences among prior reports. These findings of complementation of the locomotor effects of DAT KO by reducing 5-HT(1B) receptor activity underscore roles for interactions between specific 5-HT receptors and dopamine (DA) systems in basal and cocaine-stimulated locomotion and support evaluation of 5-HT(1B) antagonists as potential, non-stimulant ADHD therapeutics.